Zauberdiagnose und Schwarze Magie in Mesopotamien - Thomsen, Marie-Louise (1987)
The Carsten Niebuhr Institute of Ancient Near Eastern Studies; Quellen: AMT 7, 31, 44, 48, 50, 85, 86, 88, 92; ВАМ 140, 190, 203, 205, 214, 237, 434, 449, 458, 461, 464, 499; BMS 12; KAR 32, 70, 72, 80, 134; LKA 9, 102; Maqlû; SBTU II 22; STT 102, 275, 280; TDP S. 24, 176, 218f.; UET VI/2 410.